Radioactivity assessment of radium and radon concentrations in water sources at and near selected former uranium mines in the West-Rand area of Johannesburg - Tsewu, Ayabulela (My University, 2021)
The present work aimed at establishing the extent and distribution of the ac tivity concentration levels of 238U daughter-nuclides; 226Ra and 222Rn in the West Rand-area of Johannesburg. The main motive was to ascertain whether the exposure of the nearby residents to ionising radiation due to former mining activities was within the maximum acceptable limit of 1.0 mSv/y for the pub lic. Measurements include the use of Alpha Spectroscopy system (Canberra) with Passivated Implanted Planar Silicon (PIPS) and Solid-state Alpha De tectors for Radon measurements (RAD-7) to identify radionuclides, quantify and analyze isotopes of interest. A seasonal collection of 32 water samples from the mining areas was car ried out and analysed for 226Ra and 222Rn. The higher and lower radium ( 226Ra) concentration values in water samples recorded at Ezulwini inlet in winter (June 2019) and Kloof down in Summer (December 2019) found to be (164.42±18.47) mBq/l and (-3.38±-2.39) mBq/l, respectively. The average ra dium concentration for the water samples survey in the West-Rand area was 73,4±10,0 mBq/l, 74,6±9,6 mBq/l, 71,6±10,5 mBq/l, and 60,9±5,8 mBq/l for June 2019, September 2019, December 2019 and March 2020, respectively. The 226Ra activity concentration (mBq/l) of analysed samples mean values are not significantly different (p>0.05) from June 2019 to March 2020 consecutive seasons. The comparison of the mean values within pair of groups shows no statistical significance. The radium values were lower than the suggested max imum contamination levels by US-EPA of 555 mBq/l [1]. The measurements show that the radon (222Rn) concentration higher and lower values were recorded at (Bly6) Blyvooruitzicht shaft 6 discharge in Au tumn (March 2020) and (Ezul) Ezulwini Outlet discharge in Winter (June 2019) and found to be 289±272 mBq/l, and 37.1±74.1 mBq/l, respectively. The average radon concentration for the water samples survey was 142,1±79,8 iii mBq/l, 126.2±95.1 mBq/l, 134.2±108.9 mBq/l, and 140.6±123 mBq/l for June 2019, September 2019, December 2019 and March 2020, respectively. The obtained 222Rn concentration results in drinking water samples in the current study are low than the approved maximum contamination level (MCL) 11.1 Bq/l as approved by US-EPA [1]. The obtained average values for radium annual effective dose (AEDRa) were found to be 1,06E-02 mSv/y, 1,46E-02 mSv/y, 1,47E-02 mSv/y, and 1,07E+02 mSv/y from June 2019 to March 2020, respectively, while the radon annual effective dose (AEDRn) averages were 8.53E-05 mSv/y, 7.57E-05 mSv/y, 8.05E 05 mSv/y, and 8.44E-05 mSv/y June 2019 to March 2020, respectively. The maximum AEDRa value found at Bly4 in December 2019 (Summer) was 3.19E 02 mSv/y. Meanwhile, the maximum AEDRn effective dose value was found in drinking water sample (Drink) in March 2020 (Autumn) as 3.38E-04 mSv/y. The radon annual ingestion dose from the current study is lower than the European Commission and the World Health Organization proposed concen tration of 222Rn in drinking water of 100 Bq/l [2]. The results of this study indicate that the total annual effective doses from possible intake of 226Ra and 222Rn radionuclides in sampled water in West-Rand area are found below the World Health Organisation (WHO) recommended limit of 0.1 mSv/y as well as the average radiation dose of 0.29 mSv/y received per head worldwide due to ingestion of natural radionuclides assessed by UNSCEAR (2000) [3]. Finally, the physico-chemical properties of water samples such as pH and electrical conductivity (EC) are studied for all the surveyed seasons. The pH averaged 1.18, 0.94, 1.13 and 1.20 for Winter (June 2019), Spring (September 2019), Summer (December 2019) and Autumn (March 2020) seasons, respec tively. Also, the EC averaged 3134, 5566, 2872, and 3086 mS/m for Winter (June 2019), Spring (September 2019), Summer (December 2019) and Au tumn (March 2020) seasons, respectively. Above all, no significant health risk may be posed on the population surrounding the West-Rand area from 226Ra and 222Rn radionuclides present in the water samples as indicated in obtained results.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science to the Faculty of Science, School of Physics, University of the Witwatersrand, Johannesburg, 2021